Estratégia de operações: estudos de caso em revendas de gás LP em cidades do nordeste do Brasil - Muniz, Luiz Fabiano de Oliveira (2014)
One of the key factors for a successful resale of gas has, besides the relevant issues to any type of business it is maintaining a strategy aligned operations in which the Company Distributor maintains trade relations. Besides helping in the success of business strategies Distributor, resale becomes an agent of accomplishment and execution of the sale, despite its absolutely independent management. The goal of any organization, regardless of what it proposes to accomplish is to survive. But to enable such condition is very critical to have clearly defined what your positioning, as well as necessary for its operation presents a position to deliver the requirements sought by their customers attributes. In other words, this means that for an organization to be successful, it must, among other factors, the establishment of a goal to be achieved, the identification and understanding of the characteristics of competitors, differential required for operation and development of capabilities and new differential. This work aimed to study how dealers three gas companies, in northeastern Brazil, faithful to the same distributor develop their strategies and operations which the results obtained by them. To achieve this goal, first a literature able to support the development of a theoretical framework in order to develop a thorough knowledge of the subject studied and to establish a conceptual framework focused on field research, which was composed of studies was conducted case of exploratory and qualitative performed in each of the companies analyzed. After the description of the individual case studies, a cross was made of the results obtained, which were compared to identify similar characteristics and differences between companies. It was found that among the retailers studied, those with the highest level of integration with the distributor have trained to generate the expected results for its owners operating their function. In addition, issues such as defining strategic priorities, better level of service, investments and consistent development of decision areas become more favorable than that which does not share the same degree of integration.